Trends in incidence and mortality of prostate cancer in Ningbo City from 2011 to 2023 - ZHANG Qun，WANG Yong，CHEN Jieping，BAO Kaifang，FENG Yueyi，Wang Xiaoli (预防医学)
Objective: To analyze the trends in incidence and mortality of prostate cancer in Ningbo City, Zhejiang Province, so as to provide insights into the prevention and control of prostate cancer. Methods: Data of the incidence and mortality of prostate cancer in Ningbo City from 2011 to 2023 were collected through Ningbo Chronic Disease Collaborative Management System. The incidence and mortality of prostate cancer were calculated and standardized by the data from the sixth national population census in 2010 and the Segi's world standard population in 1960. The trends in incidence and mortality of prostate cancer were evaluated using average annual percent change (AAPC). Results: A total of 15 411 cases of prostate cancer were reported in Ningbo City from 2011 to 2023, and the crude incidence, Chinese-standardized incidence and world-standardized incidence were 39.62/105, 22.18/105 and 16.49/105, respectively, showing upward trends (AAPC=14.782%, 10.390% and 10.608%, all P<0.05). The Chinese-standardized incidence of prostate cancer was higher in urban areas than in rural areas, and both showed upward trends (25.14/105 vs. 19.44/105; AAPC=9.057% and 14.272%, both P<0.05). The crude incidence of prostate cancer in the groups aged 50-<60 years, 60-<70 years, 70-<80 years and ≥80 years showed upward trends (AAPC=11.657%, 14.031%, 10.734% and 5.300%, all P<0.05). A total of 3 739 deaths were reported, and the crude mortality, Chinese-standardized mortality and world-standardized mortality were 9.66/105, 5.23/105 and 3.71/105, respectively, showing upward trends (AAPC=8.458%, 3.620% and 3.602%, all P<0.05). The Chinese-standardized mortality of prostate cancer was higher in urban areas than in rural areas, and both showed upward trends (5.35/105 vs. 5.13/105; AAPC=3.183% and 3.962%, both P<0.05). The crude mortality of prostate cancer the groups ageds ≥80 years showed an upward trend (AAPC=7.482%, P<0.05). Conclusions: From 2011 to 2023, the incidence and mortality of prostate cancer in Ningbo City showed upward trends. Special attention should be paid to urban residents, and prostate cancer screening should be strengthened among males aged 50 years and older.